Métisse blanche de Kim&#8239Lefèvre, ou la rémanence des images - Jack A. Yeager (Continents manuscrits)
In 1989 Kim Lefèvre published her renowned autobiography Métisse blanche, which recounts the difficulties of being bi-racial during the colonial period. In the years preceding her death in 2021, she was writing a new panel of her unfolding autobiographical screen, inspired by her Parisian life during the first months following her arrival in France in 1960. She called the manuscript “Le Territoire du père.” In its links with Métisse blanche, this unpublished text may be read from multiple perspectives: as a corrective to what the young protagonist had learned about French culture in her native country, as an example of culture shock, as a straightforward continuation of the previous text, as a new test of her courage, or as an assertion of her own agency. The study of certain episodes from the published text and two unpublished versions of a stay in Switzerland will enable us to discern the emotional and stylistic evolution of Kim Lefèvre.